Preliminary information on parasitization rates and larval survival of Metaphycus helvolus Comp. and Metaphycus lounsburyi How., parasites of Saissetia oleae Olivier, under laboratory conditions - Macropodi, Μ. V. (ENTOMOLOGIA HELLENICA, 1985)
Parasitization rates and larval mortality of M. helvolus and M. lounsburyi parasites of S. oleae were studied under laboratory conditions. Mean life duration of M. helvolus, under temperature 23±1oC and relative humidity 65-70%, was found to be 8.4 days. Only a relatively small proportion of the individuals of S. oleae was parasitized, but the greater proportion of the larvae of the parasite was successfully developed to the adult stage. Mean life duration of M. lounsburyi, under temperature 19±1oC and relative humidity 65-70%, was found to be 10.2 days. Oviposition of M. lounsburyi occurred at a much higher rate but the fact that several eggs were usually laid per S. oleae individual greatly reduced the proportion of the parasitic larvae which developed to the adult stage.